Efficacy and safety of single dose of Non-animal stabilized hyaluronic acid intraarticular injection for knee Primary osteoarthritis: a pilot study at Midnapore Medical college in West Bengal - Gantait, Kripasindhu; Molla, Kalimujjaman; Elango, Akshaya (International Journal of Research in Medical Sciences, 2021)
Background: Hyaluronic acid is a commonly prescribed intra-articular (IA) therapy for knee primary osteoarthritis (OA). In India majority of population lives in rural areas having limited resources and socio-cultural biodiversity. Their personal, socio-cultural and occupational habits vary and need to be addressed. The primary outcome measure was pain of knee joint reduction after therapy and follow up visit. Secondary outcomes were therapy related adverse events (AEs). Methods: Population (n=20) are selected from rural areas of age range 40 to 60 years having poor economic background and daily labour by profession. Participants with diabetes and cardic illness and BMI ≥30 were excluded. All participants were having grade- 2 B/L knee OA with mild effusion and fulfill the ACR classification criteria. Each participant was assessed on Visual analog scale (VAS) pain and Composite indian functional knee assessment scale (CIFKAS) at the end of three months of therapy and statistical analysis was done. Results: Among the 20 participants 11 were female, 9 were male. The mean (mean±S.D.) of BMI and duration of disease was 23.6±2.73 and 4±2.08 respectively. Pearson correlation coefficient calculated for pain during physical activity/ pain during functional ADL activity, ability to perform physical activity/ ability to perform ADL activity and social function and emotional function score were 0.634/0.701, 0.731/0.687 and 0.566/0.607 respectively which indicates that they are highly correlated. Conclusions: A single dose of IA NASHA is effective and safe in reducing pain and functional disability in patients with primary OA of knee.